Designing a sustainable and cost-efficient energy system : a feasibility study at Rusape General Hospital in Zimbabwe - Andersson, Frida; Ulfsparre, Emma (SLU/Dept. of Energy and Technology, 2019)
Zimbabwe suffers from power outages due to reduced electricity generation from the two main energy sources coal- and hydropower. Even though the electricity supply to the hospital are highly prioritized during these blackouts, the electricity is not enough to power them all. The country has faced problems with lack of fossil fuel availability and high fuel prices. This report focuses on Rusape General Hospital in the Makoni district which is grid-connected and has diesel generators as a backup system. The aim of this project was to perform a feasibility study and examine how a sustainable energy system at the hospital would look like to reduce the power outages. A system which would be driven by solar power and uses batteries as a backup system was investigated. It was a comparison between the current system and two potential future systems with renewable energy. One of the most critical areas is the maternity ward including an operating room, which is highly prioritized among the departments at the hospital. The project examined how the energy system would look like whether the energy production covered the entire hospital or only the maternity ward. The information needed for the project was collected during a study visit of eight weeks at the hospital through interviews and a questionnaire formula. This was in a collaboration with Family Action for Community Empowerment in Zimbabwe and Engineers Without Borders. To analyse the different systems a software called HOMER Pro was used for the simulations. It gives the most cost-efficient energy production for a given system. Through simulations, the most cost-efficient solution for the entire hospital was a system with photovoltaic (PV) panels, Lithium-Ion batteries and the existing diesel generators, called System 1 in this paper. It resulted in an energy production of 131 112 kWh annually from the PV panels alone and required an installed capacity of 81.1 kW. The suggested system for the maternity ward is called System 2, with PV panels and Lithium-Ion batteries. The energy production from PV panels was in this case 7102 kWh annually and corresponded to an installed capacity of 4.43 kW. The challenges for these two suggested systems would be the lack of installers in the country, how the global warming will affect the temperature sensitive components in the future, the high investment costs and the variations of the electric load at the hospital.